Maintaining Efficiency while Integrating Entrants from Lower Performing Groups: an Experimental Study. (25th April 2016) - Salmon, Timothy C.; Weber, Roberto A.
Abstract : Efficiently growing a group often requires integrating individuals from lower performing entities. We explore the effectiveness of policies intended to facilitate such integration, using an experiment that models production as a coordination game. We create an efficient group and an inefficient one. We then allow individuals to move into the efficient group under different mechanisms. We investigate the use of an entry quota, an entry quiz and combinations of the two in order to try to understand if and why the institutions are effective. We find that both restrictions work to maintain efficient coordination but they are effective for different reasons.